Dynamism in the Features and Practices of African Religion in Yoruba Land - Akintan, Oluwatosin Adeoti (NIU Journal of Humanities, 2020)
Africa, with a very rich cultural heritage of what past generation of African people thought, did experienced and passed on to their children comprises several clans which are bound together by languages, traditions, religious observances, beliefs and practices. Undergirded with this cultural richness is religion which is the richness part of her cultural heritage. Significantly, there are many people both in the academia and the larger society who still treat African Religion derogatorily because they lack information or sound knowledge of the distinctive features and practices of the Religion. The influence of Christianity and Islam has also affected the religion negatively, to a large extent, as the adherents of these faiths even in this century still refer to the adherents of African Religion as ‘unbelievers’, ‘idol worshippers’ or ‘pagans’. It becomes pertinent therefore to write about the diversity, features and practices of African Religion in order to educate, inform and, to some extent, influence the orientation of the people of other faiths towards the religion positively. The paper therefore examined the features, nature and some of the African practices which constitute the religious beliefs of the Africans, as well as the effects of these religious beliefs and practices on the African ways of life despite the dominance of Christianity, Islam, Science and Technology. The research adopted a descriptive method and content analysis of literature on African Religion to advance the cause of the religion. The Paper concluded that despite the fact that African religion has many forces militating against it and undermining its importance in this modern age, it has evolved with time, and its many changes have positively impacted the religious, spiritual, social, moral, political and educational life of the African people. Keywords: Cultural Heritage, African Religion, Religious Observances, Modern Age.